Analysis The Effect of e-Budgeting and Government Internal Control System on The Quality of Financial Reporting of Local Government in Indonesia in Islamic Perspectives - Setyawan, Wahyu; Rika Gamayuni, Rindu; Muhammad Ahmad, Shamsuddeen (Universitas Islam Negeri Raden Intan Lampung, 2019)
The objective of this study is to determine the impact of e-budgeting and internal government control systems to financial reporting of local governments in Indonesia as measured by the achievement of the unqualified opinion from the report of the Financial Audit Board (LHP BPK) on the Regional Government Financial Reports (LKPD). Financial reporting is a mechanism in the delivery of financial information and a representation of the financial position of transactions carried out by local governments , as an obligation of responsibility for the allocation and use of resources that are useful for accountability and transparency purposes.The implementation of e-budgeting and the government internal control system in the preparation of financial reporting is a means to realize accountability and transparency in governance in bureaucratic reform. This is consistent with the perspective of Islam provides guidance in the embodiment of the system of good governance government in the form of three pillars, namely transparency , accountability and participation . The study population was all local governments in Indonesia with a sample that local governments in Indonesia are already implementing e-budgeting in the 2017 -2018 . This research method is a quantitative empirical research method using secondary data with data analysis performed statistical tests using multiple linear regression with Eviews 9.0. The results of hypothesis testing and multiple regression analysis with eviews 9.0 shows that e-budgeting and government internal control systems are simultaneously influenced positively to financial reporting of local governments in Indonesia in the form of unqualified opinion. Keywords : E-Budgeting, Government Internal Control, Financial Reporting, Islamic Perspective.